Designing stakeholder learning dialogues for effective global governance - Benjamin Cashore; Steven Bernstein; David Humphreys; Ingrid Visseren-Hamakers; Katharine Rietig (Policy & Society, 2019)
A growing scholarship on multistakeholder learning dialogues suggests the importance of closely managing learning processes to help stakeholders anticipate which policies are likely to be effective. Much less work has focused on how to manage effective transnational multistakeholder learning dialogues, many of which aim to help address critical global environmental and social problems such as climate change or biodiversity loss. They face three central challenges. First, they rarely shape policies and behaviors directly, but work to ‘nudge’ or ‘tip the scales’ in domestic settings. Second, they run the risk of generating ‘compromise’ approaches incapable of ameliorating the original problem definition for which the dialogue was created. Third, they run the risk of being overly influenced, or captured, by powerful interests whose rationale for participating is to shift problem definitions or narrow instrument choices to those innocuous to their organizational or individual interests. Drawing on policy learning scholarship, we identify a six-stage learning process for anticipating effectiveness designed to minimize these risks while simultaneously fostering innovative approaches for meaningful and longlasting problem solving: Problem definition assessments; Problem framing; Developing coalition membership; Causal framework development; Scoping exercises; Knowledge institutionalization. We also identify six management techniques within each process for engaging transnational dialogues around problem solving. We show that doing so almost always requires anticipating multiple-step causal pathways through which influence of transnational and/or international actors and institutions might occur.